Injury and illness in World Taekwondo junior athletes: An epidemiological study - Jeong, H. S.; Ha, S.; Jeong, D. H.; O`Sullivan, D. M. (International Journal of Environmental Research and Public Health, 2021)
Taekwondo has been reported to be one of the most injurious sports in the summer Olympics, however, there is a dearth of data about injury profiles for junior athletes. Therefore, we aimed to identify the incidence and profiles of the injuries and illnesses that occurred during the 2018 World Taekwondo Junior Championships and recorded using an online system. Among the 889 athletes, 67 injuries and four illnesses were reported, corresponding to an overall clinical incidence of 7.5 injuries (95% confidence interval [CI]: 5.7-9.3) and 0.5 illnesses (0.1-0.9) per 100 athletes. The most frequent injuries were lower extremity injuries (n = 33, 3.71% of all athletes), mostly in the foot/toe (n = 11, 1.2% of athletes), followed by head and trunk injuries, mostly in the face (n = 14, 1.6% of athletes), and upper extremity injuries, mostly in the fingers (n = 6, 0.7% of athlete). Contusions (n = 37, 4.2% of athlete) were the most frequent injury type, followed by ligament ruptures/sprains and laceration. The most common injury mechanism was contact during an opponent attack (n = 51, 5.7% of athlete). Three mild concussions none resulted in time loss (none required hospital transfer or had prolonged recovery). The respiratory system was the most affected by illness, with pain and fever as symptoms. Environmental factors were the most common cause of illness. This study shows that 7.5 per 100 athletes (38.5/1000 athlete-exposures and 6.9/1000 min-exposures) had new or recurrent injuries, whereas 0.5 per 100 athletes experienced illness. In conclusion, the data shows male athletes reported more injuries than females and the most common cause of injury was due to contact between athletes. Contusions, ligament rupture/sprains, laceration and fractures to the lower extremities, head, and trunk were the most common injury. Knowing these injury profiles of junior taekwondo athletes can help taekwondo stakeholders, especially medical staff to prepare accordingly to ensure the safety of the athletes.